Dionysus resurrected : performances of Euripides' 'The Bacchae' in a globalizing world - Fischer-Lichte, Erika (Chichester : Wiley-Blackwell, 2014)
Dionysus Resurrected analyzes the global resurgence since the late 1960s of Euripides’ The Bacchae. By analyzing and contextualizing these modern day performances, the author reveals striking parallels between transformational events taking place during the era of the play’s revival and events within the play itself.

* Puts forward a lively discussion of the parallels between transformational eventsduring the era of the play’s revival and events within the play itself
* The first comparative study to analyse and contextualize performances of The Bacchae that took place between 1968 and 2009 from the United States, Africa, Latin America, Europe and Asia
* Argues that presentations of the play not only represent liminal states but also transfer the spectators into such states
* Contends that the play’s reflection on various stages of globalization render the tragedy a contemporary play
* Establishes the importance of The Bacchae within Euripides’ work as the only extant tragedy in which the god Dionysus himself appears, not just as a character but as the protagonist
Sadržaj: Preface ; Introduction: Rediscovering 'The Bacchae' ; Part 1: Festivals of liberation : celebrating communality ; Part 2: Renegotiating cultural identities ; Part 3: Productive encounter pf destructive clash of cultures?
Bibliografije uz poglavlja.
Imensko kazalo ; Predmetno kazalo
Keywords: teorija drame; antička drama - moderne izvedbe; Euripides -- Bakhe